Prevalence of pressure ulcers among the elderly living in long-stay institutions in São Paulo - Chacon, Julieta Maria Ferreira; Blanes, Leila; Hochman, Bernardo; Ferreira, Lydia Masako (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: The prevalence of pressure ulcers varies according to geographic region and population group, such as the institutionalized elderly. The aim of this study was to identify the prevalence of pressure ulcers among elderly people living in long-stay institutions. DESIGN AND SETTING: Cross-sectional study in six long-stay institutions for the elderly in São Paulo, Brazil. METHODS: Demographic and clinical data were collected in six long-stay institutions on two visits to each institution between May and August 2007, during which all elderly patients with pressure ulcers were evaluated. The Braden scale was used to identify the risk of developing pressure ulcers and the National Pressure Ulcer Advisory Panel (NPUAP) stages for classifying the pressure ulcers. Statistical analysis was performed using the chi-square test, Student’s t-test and Fisher’s exact test. RESULTS: There was no significant difference in the results between visits. The population was 181 elderly people in May and 184 in August: 23 had pressure ulcers in May (prevalence of 12.7%) and 17 in August (prevalence of 9.2%). The mean age at the two times was 84 years, and the average length of stay was 32 months. Pressure ulcers were found mainly in the sacral region (mean, 71.5%), and most commonly in stage II (mean, 41%). CONCLUSION: The prevalence of pressure ulcers was 10.95%. These data provide background information that may aid in developing protocols for applying best practices for prevention and treatment of pressure ulcers, consequently reducing the prevalence.